ERNÄHRUNG & KÖRPERLICHE AKTIVITÄT - Carlsohn A; 2 (Dynamic Media Sales Verlag, 2016)
Athletes may support health, training adaptations and performance by generally adequate diets and a prudent nutrient timing. However, for endurance athletes some obsolete recommendations and dietary myths are still widespread among recreational and elite athletes, coaches and health care professionals. This includes hydration strategies as well as nutrient intake before, during and after exercise. In addition, dietary recommendations for elite endurance athletes might differ in some aspects from nutrition recommendations for the general population including recreational athletes. Thus, this article aims to summarize the recent nutritional guidelines for endurance athletes during different training periods and to distinguish between elite and recreational endurance athletes where possible. Finally, some nutrition-associated clinical issues observed in endurance athletes are presented and dietary recommendations to reduce the risks are provided.To summarize, meeting the energy requirement is the major nutritional goal in endurance athletes. Energy availability should not fall below 30-45kcal/kg fat-free mass/d. Carbohydrate requirements vary from 3-5g/kg/d during low-intensity up to 8-12g/kg/d in high-intensity, high-volume training periods. Protein requirements of elite athletes are approximately twice as high as those ofsedentary people or recreational athletes, but not higher than the average protein intake of the general population in Germany (1.4-1.6g/kg/d). Health care professionals (e.g. nutritionists at the Olympic Sports Centers) may help endurance athletes to follow a healthy diet with prudent food choices and clever nutrient timing.KEY WORDS: Nutritional Guidelines, Nutrient Intake, Rehydration, Endurance Athletes